Three-dimensional perfused tumour spheroid model for anti-cancer drug screening - Wan, X; Li, Z; Ye, H; Cui, Z (Springer Netherlands, 2016)
Objective To build up an in vitro perfused three-dimensional (3D) spheroid model based on the TissueFlex® system for anti-cancer drug efficacy testing, to closer mimic avascular micro-tissues with inherent oxygen, nutrient and metabolite gradients, and to provide more accurate prediction of drug toxicity and efficacy than traditional in vitro tumour models in conventional static culture well plates. Results The perfused cancer spheroid model showed higher cell viability and increased diameter of spheroid over a relatively long culture period (17 days). Three anti-cancer drugs with different cytotoxic mechanisms were tested. In perfusion, lower cytotoxicity was observed for traditional cytotoxic drug 5-fluorouracil (5-FU), and microtubule-interfering Paclitaxel showed more spheroid integrity interruption. For the hypoxic-dependent drug, tirapazamine (TPZ), there was no significant difference observed between static and perfusion cultures. Conclusion The perfused cancer spheroid model showed higher cell viability and increased diameter of spheroid over a relatively long culture period (17 days). Three anti-cancer drugs with different cytotoxic mechanisms were tested. In perfusion, lower cytotoxicity was observed for traditional cytotoxic drug 5-fluorouracil (5-FU), and microtubule-interfering Paclitaxel showed more spheroid integrity interruption. For the hypoxic-dependent drug, tirapazamine (TPZ), there was no significant difference observed between static and perfusion cultures.